1991
DOI: 10.1007/bf02576687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive end-expiratory pressure (PEEP) ventilation on the exocrine pancreas in minipigs

Abstract: The effect of positive end-expiratory pressure (PEEP) ventilation on the pancreas was studied in 22 anesthetized minipigs. Five pigs were treated with intermittent positive pressure ventilation (IPPV) for 21 h (Group I) and six pigs were treated with a PEEP of 15 cm H2O for 21 h (Group II). We next explored the influence of PEEP ventilation while stimulating the pancreas with Ceruletide, a synthetic cholecystokinin (CCK) analog, at 2.3 micrograms/kg per h.i.v. for 3 h. Ventilation with IPPV for 4 h (n = 5, gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Acute lung injur y and respirator y failure are frequent and potentially fatal complications of acute pancreatitis [15,16] . Impor tantly, the institution of positive pressure mechanical ventilation can itself induce acute pancreatitis by exacerbating splanchnic hypoperfusion [1,17] . Recent studies have reported that elevated serum lipase levels are frequently encountered in critically ill patients, and hypoperfusion and inflammatory processes associated with multiple-organ failure appear to result in pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lung injur y and respirator y failure are frequent and potentially fatal complications of acute pancreatitis [15,16] . Impor tantly, the institution of positive pressure mechanical ventilation can itself induce acute pancreatitis by exacerbating splanchnic hypoperfusion [1,17] . Recent studies have reported that elevated serum lipase levels are frequently encountered in critically ill patients, and hypoperfusion and inflammatory processes associated with multiple-organ failure appear to result in pancreatitis.…”
Section: Introductionmentioning
confidence: 99%